LAMA WAKTU PERENDAMAN BIJI PALA (Myristica fragrans H.) DENGAN PENAMBAHAN KALIUM NITRAT (KN03) TERHADAP PERKECAMBAHAN BIJI - Savanah Zahra; Mayta Novaliza Isda (Universitas Lancang Kuning, 2023)
Myristica fragrans Houtt. is a spice plant that is used as a spice in the kitchen, food preservatives, beverages, perfumes, cosmetics and soaps. The large use of nutmeg plants results in high industrial demand for nutmeg but the availability of nutmeg is minimal because generative propagation using seeds is still constrained because the structure of the seed coat is hard so that germination takes up to 8 weeks. Dormancy breaking can be done with chemical compounds such as the use of KN03 (potassium nitrate). This study aims to determine the effect of soaking time of nutmeg using KN03 solution and determine the efficient time of soaking nutmeg using KN03 solution on germination. This study used a completely randomized design (CRD) which consisted of 5 levels of immersion time, namely without immersion KN03, immersion 12 hours, 24 hours, 36 hours and 48 hours. Parameters observed were germination percentage and germination time. Data were analyzed using ANOVA at 5% level and DMRT follow-up test. The results showed that the duration of soaking nutmeg seeds using KN03 had a significant effect on the percentage of germination and germination time. The treatment of soaking nutmeg seeds with 2% KNO3 for 24 hours was an efficient treatment for nutmeg seed germination with a germination percentage of 88.3% and germination time of 23.7 days.